Oral Azithromycin Pulse Therapy and Daily Topical Benzoyl Peroxide in the Treatment of Acne Vulgaris: An Open Clinical Trial Study - Akter, Bilqis (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Introduction: Combination therapy is an effective approach to simultaneously target multiple pathogenic factor of acne. A unique combination of oral azithromycin pulse therapy and daily topical benzoyl peroxide has been developed for treatment of acne. Material & Methods: It was an open, controlled, clinical trial, conducted on 37 out patients with acne vulgaris. Patients were clinically assessed at baseline &at week 0,4, 8 and 12. Evaluation included success rate (subjects clear or excellent improvement, good response), lesion count & percentage change in lesion count from baseline, cutaneous tolerability & adverse events. Results: The combination of oral azithromycin pulse therapy & daily topical benzoyl peroxide was very safe & effective with significant differences in percentage of lesion count change observed as early as 1-4 weeks .Adverse events were more frequent with the combination therapy that occurred early in the study &were transient. Conclusion: This study revealed that combination regimen of azithromycin &benzoyl peroxide (4%) is indeed very much efficacious & safe in the management of acne vulgaris. J Bangladesh Coll Phys Surg 2018; 36(1): 11-15